Clinical study of intra-abdominal abscess and its management by percutaneous USG guided drainage - Dhurve, Asmita S.; Bodade, Ritesh M.; Bugga, Raunak R.; Nandu, Vipul V.; Meshram, M. M. (International Surgery Journal, 2018)
Background: Intra-abdominal abscesses continue to present therapeutic challenge to the surgeon. They are common complication of inflammatory bowel disease, malignancy and trauma. The objective of the present study is to manage the intra-abdominal abscesses by percutaneous aspiration under ultrasound guidance and placement of continuous catheter drainage wherever deemed necessary and to assess the efficiency, limitations and complications, if any of this method. Methods: A total of 120 cases of intra-abdominal abscesses were selected. The diagnosis of intra-abdominal abscess was confirmed by USG and/or CT. Patients were then subjected to ultrasound guided drainage/aspiration as a therapeutic measure. Post procedure patients were watched for signs of peritonitis. Systemic antibiotics were given, and analgesics were given on SOS basis. Follow up ultrasound after three days was done. Follow up was kept in all cases. Results: Most common occurring intra-abdominal abscesses were liver abscess (60.83%) and sub-diaphragmatic abscess (11.67%). The etiology was not known i.e. cryptogenic in 47.5% and occurring post-surgically were 28.33%. In 25% patients, single aspiration was sufficient. In 30.80% patients, 2 aspirations and in 29.12% patients, 3 aspirations were needed. 72.5% patients were successfully treated by aspiration only and in the remaining 27.5% patients drain was kept. The complication rate was 7.5%. [Bleeding-0.83%, recollection-1.67% and damage to viscera-0.83%, which were related to the procedure]. Conclusions: The method is associated with good success rate, low morbidity and mortality, better patient compliance, low cost, can be performed under local anaesthesia and even in critically ill and high-risk patients and should be used as an initial procedure in the treatment of intra-abdominal abscesses.